The presence of multiple copies of the vitellogenin gene in Fenneropenaeus merguiensis (De Man, 1888) (Decapoda: Dendrobranchiata: Penaeidae): Evidence for gene expansion and functional diversification in shrimps. Issue 1 (4th February 2021) - Zhao, Jichen; Wang, Wei; Wang, Chenggui; Shi, Lili; Wang, Gang; Sun, Chengbo; Chan, Siuming F
Abstract: Vitellogenin (Vg) is the precursor of egg yolk that provides nutrients to embryos of oviparous animals. We identified three Vg genes (FmVg1, FmVg2, and FmVg3) from the banana shrimp Fennerpenaeus merguiensis (De Man, 1888 ) (Penaeidae). The cDNAs ranged from 7, 758 to 7, 764 bp, and the encoded protein consisted of 2, 553–2, 585 amino acid residues. The genome structures of FmVg1, FmVg2, and FmVg3 were highly conserved, containing 15 exons and 14 introns. FmVg1-FmVg2, FmVg1-FmVg3, and FmVg2-FmVg3 shared a moderate 52.25%, 60.77%, and 56.45%, respectively. Phylogenetic analysis further revealed that the FmVg1 class vitellogenins are more conserved among the shrimps. The expression patterns of FmVg1, FmVg2, and FmVg3 were similar in the hepatopancreas at different ovarian developmental stages, whereas the expression trends between FmVg1 and FmVg2/3 in the ovary were remarkably different. During ontogenic development, the expression of these Vg genes all reached the highest levels at the post-larval stage. The three Vg genes also exhibited dynamic expression changes at different molting stages, with the highest expression level detected at the intermolt stage. Our study provides evidence that at least three copies of the Vg gene are present in the banana shrimp. These Vg genes are potentially involved in ovary maturation and larval development, and the divergence in their sequences, structures, and expression dynamics reflects their functional diversification in F. merguiensis . The expression of these Vg genes is therefore tightly regulated spatially and temporally. This is the first report for the molecular characterization of multiple vitellogenin genes in shrimps. Our results indicate that the vitellogenin gene is multi-functional and shows a non-sex specific expression pattern.